3,5-Diiodo-l-Thyronine Increases Glucose Consumption in Cardiomyoblasts Without Affecting the Contractile Performance in Rat Heart - Sacripanti, Ginevra; Nguyen, Nhat Minh; Lorenzini, Leonardo; Frascarelli, Sabina; Saba, Alessandro; Zucchi, Riccardo; Ghelardoni, Sandra (Frontiers in Endocrinology, 2018)
3,5-diiodo-L-thyronine (T2) is an endogenous derivative of thyroid hormone that has been suggested to regulate energy expenditure, resting metabolic rate and oxygen consumption with a mechanism that involves the activation of mitochondrial function. In this study, we focused on the cardiac effects of T2, which have been poorly investigated so far, by using both in vitro and ex-vivo models. As a comparison, the response to T3 and T4 was also determined. Rat cardiomyoblasts (H9c2 cells) were used to determine T2, T3 and T4 uptake by High Performance Liquid Chromatography-tandem Mass Spectrometry. In the same experimental model, MTT test, crystal violet staining and glucose consumption were investigated, using T2 concentrations ranging from 0.1 to 10 μM To assess cardiac functional effects, isolated working rat hearts were perfused with T2, T3 or T4 in Krebs-Ringer buffer , and the hemodynamic variables were recorded. T2 was taken up by cardiomyoblasts, and in cell lysate T2 levels increased slowly over time, reaching higher concentrations than in the incubation medium. T2 significantly decreased MTT staining at 0.5-10 µM concentration (P<0.05) Crystal violet staining confirmed a reduction of cell viability only upon treatment with 10 µM T2, while equimolar T3 and T4 did not share this effect. Glucose consumption was also significantly affected, as indicated by glucose uptake being increased by 24% or 35% in cells exposed to 0.1 or 1.0 µM T2 (p<0.05 in both cases). On the contrary, T3 did not affect glucose consumption which, in turn, was significantly reduced by 1 and 10 µM T4 (-24% and -41% vs control, respectively, P<0.05 and P<0.01). In the isolated perfused rat heart, 10 µM T2 produced a slight and transient reduction in cardiac output, while T3 and T4 did not produce any hemodynamic effect. Our findings indicate that T2 is taken up by cardiomyoblasts, and at 0.1-1.0 µM concentration it can modulate cardiac energy metabolism by increasing glucose consumption. Some evidence of toxicity and a transient impairment of contractile performance is observed only at 10 µM concentration. These effects appear to be specific for T2, since they are not reproduced by T3 or T4.